Prevalence of aflatoxin contamination in cereals from Nandi County, Kenya - Sirma, A.J.; Ouko, E.O.; Murithi, G.; Mburugu, C.; Mapenay, I.; Ombui, J.N.; Kang'ethe, Erastus K.; Korhonen, H. (2015)
Aflatoxins are secondary fungal metabolites that contaminate cereals, other crops and animal source foods and are a recognized health risk. Kenya has had several outbreaks of aflatoxicosis affecting humans and pets. The aim of this study was to compare aflatoxin levels in cereals, the staple diet of Kenyans, in Nandi where aflatoxicosis has not been reported despite being a maize growing area. Maize, sorghum and millet were sampled from households and also from markets serving various villages in the selected sub-locations (408 samples). The samples were tested for total aflatoxin contamination using cELISA. Households in the study sub-locations depended on homegrown grains than market sourced. Sixty seven point nine percent (72/106), 73.3% (44/60) and 65.7% (67/102) of maize samples collected from Laboret, Kilibwoni and Chepkongony were contaminated with aflatoxins ranging between 0.17-5.3 parts per billion (ppb). Ninety two point nine percent (13/14), 100% (9/9) and 87.5% (14/16) of millet samples from Laboret, Kilibwoni and Chepkongony were positive for aflatoxin at a range of 0.14-6.4 ppb. Fifty percent (9/18), 36.4% (8/22) and 27.3% (6/22) of sorghum samples from Laboret, Kilibwoni and Chepkongony, respectively were contaminated with aflatoxins beyond Kenya Bureau of Standards (KEBS) maximum tolerable limits of 10 ppb. To manage aflatoxin contamination of the cereals in Nandi, the county government needs to step up awareness creation of the dangers posed by chronic aflatoxin exposure to households through cereals and promote good Agricultural practices.